Two new cunaxid mites (Acari: Cunaxidae) from Bahia state, Northeastern Brazil - Rocha, Matheus Santos; Argolo, Poliane Sá; Ferla, Noeli Juarez; Oliveira, Anibal Ramadan (Zootaxa, 2017)
Two new cunaxid mite species, namely Scutopalus acaraje Rocha & Argolo n. sp. and Armascirus raulzito Rocha & Argolo n. sp., are described and illustrated from leaves of different plants of economic and ornamental importance of Bahia state, Northeastern Brazil. This is the first record of Scutopalus for that state.